USING THE REVISED BLOOM’S TAXONOMY TO ANALYZE THE READING COMPREHENSION QUESTIONS IN EFL TEXTBOOK FOR YEAR X OF HIGH SCHOOL - Anne Irawan; Veronica Listyani Diptoadi (Widya Mandala Surabaya Catholic University, 2022)
Reading skill is an important skill in the mastery of a language as the more the students read, the more exposed they are to the target language. Giving reading comprehension questions that suit the students’ thinking level has been widely known to foster the students’ critical thinking and reading comprehension. This study aimed (1) to explore the cognitive level of the reading comprehension questions found in EFL textbook based on the Revised Bloom’s Taxonomy and (2) to explore appropriate reading comprehension questions to supplement the EFL textbook to meet the Curriculum of 2013. This study analyzed an EFL textbook for year X of high school based on the cognitive domain of the Revised Bloom’s Taxonomy. The findings show that the proportion between LOTS and HOTS questions was 85.5% and 15.5%. Considering that the EFL textbook was dominated by LOTS questions, it was concluded that the EFL textbook was not appropriate for 10th grade students. Therefore, this study proposed 84 appropriate reading comprehension questions to supplement the EFL textbook so as to allow the students to hone their reading skill through various cognitive processes. There was an increase of 20.4% in the percentage of HOTS questions after the addition of the researcher’s supplementary questions, so the proportion between LOTS and HOTS questions became 65.1% (LOTS questions) and 34.9% (HOTS questions).